1989
DOI: 10.2165/00003495-198938010-00004
|View full text |Cite
|
Sign up to set email alerts
|

Salbutamol in the 1980s

Abstract: Salbutamol (albuterol) is a beta 2-selective adrenoceptor agonist which accounts for its pronounced bronchodilatory, cardiac, uterine and metabolic effects. During the intervening years since salbutamol was first reviewed in the Journal (1971), it has become extensively used in the treatment of reversible obstructive airways disease. Numerous studies in this disease (including severe acute, childhood and exercise-induced asthma) have confirmed the bronchodilatory efficacy of salbutamol, and it has been shown t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

1992
1992
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(21 citation statements)
references
References 149 publications
0
21
0
Order By: Relevance
“…It is also used illegally as growth promoters in the liver stock industry [2]. Its residue can be toxic to humans.…”
Section: Introductionmentioning
confidence: 99%
“…It is also used illegally as growth promoters in the liver stock industry [2]. Its residue can be toxic to humans.…”
Section: Introductionmentioning
confidence: 99%
“…Salbutamol sulfate, which has the phenolic group, is a most effective inhibitor compared with other drugs. It has been reported that phenol groups are among inhibitors of paraoxonase1 enzyme . The IC 50 values of tiotropium, varenicline tartrate, and ciprofloxacin hydrochloride (0.997, 1.665, and 4.822 μM, respectively) are smaller than that of the most known potent inhibitor (2‐hydroxyquinoline < 5 μM) of the paraoxonase .…”
Section: Resultsmentioning
confidence: 99%
“…Kinetic data indicated that the inhibition types of PON1 activity by ciprofloxacin hydrochloride and ampicillin trihydrate were found as mixed (Figure ). There are several studies in the literature about the interaction between antibiotics and hPON1 . Sinan et al demonstrated ciprofloxacin and sodium ampicillin inhibition efficacy of PON1, with IC 50 values of 0.313 and 27.51 mM, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Salbutamol is a sympathomimetic drug with potent b 2 -adrenoceptor stimulating properties, widely used in the treatment of respiratory diseases and it is also applied as tocolytic agent [15]. This drug being administrated as the racemate, each enantiomer needs to be monitored separately.…”
Section: Introductionmentioning
confidence: 99%